EFFECTS OF FIXED VS REMOVABLE ORTHODONTIC RETAINERS ON PERIODONTAL HEALTH - Fareena Ghaffar; Alaina Tariq Mughal; Abdullah Jan; Rooma Shahid; Hafiza Zobia Shafique; Sundas Mehmood (Journal of Postgraduate Medical Institute, 2022)
Objective: To assess the effects of fixed and removable orthodontic retainers in a mandibular arch on periodontal health. Methodology: This study was carried out at AFID from November 2018 to November 2020. Sixty-four patients, 42 females (65%) and 22 males (34%) with a mean age of 19.46±2.01years were selected and given either vacuum formed retainer (VFR) or bonded retainer wire (BRW) in mandibular arch and divided into two equal groups. Only the mandibular arch was used to measure two clinical variables (Gingival index and calculus index) at four different time intervals, immediately after de-bonding (T0), at 6 months (T1), at 12 months (T2) and at 24 months(T3) to assess the effects of two retainer groups on Periodontal health. Results: No significant difference was found between gingival index and calculus index scores at T0 among VFR group and BRW group (p>0.05) while statistically significant differences were found in gingival index scores at T1 (p=0.025) and calculus index scores at T1 and T3 (p=0.015, p=0.048 respectively) among the two retainer groups. Conclusion: Fixed bonded retainer wire is capable of causing gingival inflammation and calculus aggregation, indicated by mild increase in gingival and calculus scores, in comparison to vacuum formed retainer. Although no adverse effects were observed on overall periodontal health with both retainers. This does not guarantee future disease progression, so careful monitoring of oral hygiene on follow-up visits should be a prime concern of orthodontists.